Aplication of Fourier series in the solution of initial value problems in the border - Fermin Flavio Mamani Condori (2019)
For the present investigation, data collection was done through books relating to the subject, which resulted in a summary. Often presents the problem of solving a partial differential equation subject to certain conditions. This leads to problems with boundary or initial value. In some cases the solutions obtained do not satisfy one of the initial conditions, however with the aid of Fourier series it is possible to identify a solution that satisfies all the conditions.In 1807, the French mathematician Joseph Fourier series Fourier introduced its most important research work, which developed the theory of heat conduction. These new series became one of the most important tools of mathematics to be widely applicable.The objective of this research is to determine a mathematical model that allows us to predict the temperature of a solid body at any future time.